Investigating multiple human performance measures in teleoperation task: A translation task in a tele-sandblasting maintenance system - Jientrakul, Ranon; Yuangyai, Chumpol; Cheng, Chen Yang; Chotiprayanakul, Pholchai; Limnararat, Sunpasit (My University, 2018)
In sandblasting tasks for complex steel structure maintenance, teleoperation is required to keep humans away from occupational risk and hazard. On the other hand, teleoperation typically degrades system-human performances, resulting in poor product quality and must be designed such that the performances remain as high as possible. However, designing the teleoperation system regarding to a single performance measure may lead to an improper design. In this article, we propose two novel loss-function-based human-performance measures to incorporate with a widely used performance measure, movement time, to thoroughly represent performance: unfinished surface and damaged surface. We aim to investigate the effects of two main design parameters, viewing distance and path width. The results show that only path width is significant for overall performances. Furthermore, the effect of gender is significant such that men outperform women in cleaning the surface. Finally, the optimal setting conditions are suggested to achieve their optimal performances.
Keywords: human performance measures; multiple responses; translation task; viewing distance